Histological and quantitative polymerase chain reaction-based analysis of Buruli ulcer using mapping biopsy method. - Toshifumi Takahashi; Miho Kabuto; Gen Nakanishi; Toshihiro Tanaka; Noriki Fujimoto (Public Library of Science (PLoS), 2020)
Background In Japan, Buruli ulcer cases are often advanced, requiring surgical treatment. However, extensive debridement is often difficult because of cosmetic and functional sequelae. Moreover, the lesions are complicated and composed of edematous erythema, necrotic ulcer, and erythematous skin lesions caused by a paradoxical reaction, which also make it difficult to perform adequate debridement. Methodology/principal findings We performed quantitative polymerase chain reaction (PCR) analysis for IS2404 using 29 samples taken from mapping biopsy. We evaluated the relationship among mycobacterial burden, histopathological findings, and clinical outcomes using 83 tissue samples taken from mapping biopsy and debrided Buruli ulcer. On quantitative PCR, the Cp values of IS2404 amplification were substantially different in each site. The major histological findings could be divided into massive subcutaneous necrosis with scant inflammatory cell infiltration and dense inflammatory cell infiltration. Of the 84 sites, 34 were subjected to repeated histological evaluations. In these sites, histological necrosis did not disappear over time despite standard antibiotic treatment. In contrast, the ulcers were cured and no recurrences were observed without resecting the 11 biopsied sites that lacked histological necrosis. Although quantitative PCR revealed that a lower Cp value of IS2404 was associated with histological massive necrosis, sites that showed lower Cp values clinically did not always need debridement. Conclusion/significance Our descriptive study revealed that the histological findings and amounts of mycobacterial DNA differed according to the sites despite being found in one lesion. Our results showed that the need for surgical debridement in each site was correlated with histological necrosis without inflammatory cell infiltration, as the inflammation is supposed to represent an active host immune response rather than mycobacterial burden. We suggest that the debridement of lesions with histological necrosis in mapping biopsy may be useful for Japanese cases with unsuccessful standard antibiotic treatment to achieve sufficient clinical improvement.